Business in troubled waters: Does adverse attitude affect firm value? - Park, Jung Chul; Sarkar, Dipanwita; Sarkar, Jayanta; Yost, Keven (Journal of Corporate Finance, 2013)
This paper investigates the relationship between US MNCs' valuations and anti-Americanism in countries where MNCs' foreign subsidiaries are located. We find that MNCs suffer value-destruction when they enter markets where people express severe anti-Americanism. However, we uncover that geographic diversification into these high anti-Americanism countries significantly increases firm value if the MNC has high levels of intangibles such as technological know-how and marketing expertise. Our findings are consistent with the notion that the advantages from internalizing the cross-border transfer of intangibles are greater when barriers to competition are higher.